Panel: Shifts In Socially Mediated Visual Cultures: Images By/For Machines And Humans - Tiidenberg, Katrin; Schreiber, Maria; Lehmuskallio, Asko; Fausing, Bent; Bechmann, Anja; Markham, Annette; Seppänen, Janne; Häkkinen, Jukka (AoIR Selected Papers of Internet Research, 2017)
Recent scholarship has pointed to significant changes in the scope and form of images generated and circulated through automated and non-automated practices. Some even go as far as to say that one of the most notable uses of the internet is to create, send and view images of all kinds; and that networked publics are moving towards more intense forms of visual interaction. A ubiquity of both human-to-human and machine-to-machine images has been credited with leading to a certain standardization of the visual landscape. While most images are never seen or noticed by human eyes, others are intensely scrutinized by vast populations, and others yet play an important part in how the world is made sense of, or in interpersonal communication and meaning making. This panel brings together five scholars of visuality to engage with shifts in socially mediated visual cultures and networked visuality. Included papers analyze everyday, professional and algorithmic practices as well as the rhetorics of visuality used by or influencing different networked publics. We look at different groups (people using Snapchat, people articulating visual social media’s affordances, professional photographers making sense of computer generated versus photographed images, deep learning algorithms and their ways of categorization, the meanings of images in a post internet world as evident in advertising discourse), but come back to the central question of how visual culture is enacted, made sense of and regulated in both automated and manual, algorithmic and intimate, professional and vernacular ways.